Computational model for timing of delivery in an obese population. (16th February 2018) - Gill, Lisa; Holbert, Michael
Abstract: Objective: To estimate the impact on stillbirth risk, cesarean deliveries, and delivery-related healthcare cost associated with induction of labor compared to expectant management of term pregnancies in an obese population. Methods: A decision analysis model was designed to compare the delivery and cost outcomes associated with a hypothetical cohort of 100, 000 term pregnancies, complicated by obesity, that were planning a vaginal delivery. The model predicted stillbirths, cesarean deliveries, and total delivery-related health care cost from routine induction at 39 weeks compared to expectant management and routine induction each week from 40 to 42 weeks. Results: There were 387 stillbirths avoided by routine induction at 39 weeks compared to the worst-case model of expectant management with induction at 42 weeks. 9234 cesarean deliveries were avoided by routine induction at 39 weeks compared to the worst-case model of expectant management and induction at 41 weeks (30, 888 vs. 40, 122) . Routine induction at 39 weeks showed a savings in delivery-related health care cost of 30 million dollars compared to the worst-case model of expectant management and induction at 41 weeks (536 million vs. 566 million). Conclusion: Utilizing this computational model, routine induction at 39 weeks minimizes stillbirths, cesarean deliveries, and delivery-related health care cost.